Distribution and Diversity of Family Rubiaceae in Pulau Banding, Gerik, Perak - Nek Adek Nik Badrul; Awang Afrina; Zulkeflee Nur Hafizah; Ismail Nur Akilah; Hamzah Zulhazman; Eh Rak Aweng; Abdul Karim Muhammad Firdaus; Amaludin Nazahatul Anis (BIO Web of Conferences, 2023)
The distribution and diversity of the Rubiaceae species were investigated along one trail at Pulau Banding, Gerik, Perak. This study aims to identify and estimate the diversity of the Rubiaceae species. The diversity and distribution of the Rubiaceae species were calculated using Shannon-Wiener’s Diversity Index, Simpson's Diversity Index and relative abundance index. A total of 139 individuals from nine species were recorded from Pulau Banding, Perak which are Mitracarpus hirtus, Gardenia carinata, Aidia densiflora, Hypobathrum hirtum, Coffea arabica, Psychotria marginata, Lasianthus constrictus, Porterandia anisophyllea and Ixora finlaysoniana. The values of the Shannon-Wiener’s Diversity Index (H′) and Simpson's Diversity Index (D) are 1.55 and 3.27, respectively. This indicates that M. hirtus is the most dominant species, encompassing 49% of all recorded Rubiaceae. Since it has many benefits such as food, timber, medicine, and the diversity of conservation value, this is vital as baseline data for researchers to propose solutions to the stakeholders and conservation sustainability of the Rubiaceae family as plant resources in Pulau Banding, Perak.